Sample learning kits for developing outlining skills among grade six pupils - Diaz, Teresita Uy 1940- (1977)
This research paper presented sample learning kits corresponding to the five requisite skills necessary to develop outlining skills. These five learning kits or tasks resulted from an analysis of a continuum or heirarchy of learning tasks leading to the development of outlining skills at the sixth grade level. The entire kit contains the statement of purpose, instructional objectives, prerequisite skills of users, diagnostic pretest/posttest, and instructions for users. A teacher's manual accompanies the learning kits. The learning kits are recommended for a field try-out, the results of which could be used as bases for refinement and revisions. These learning kits are intended for Grade VI pupils.
"March, 1977."
Vita.
Thesis (M.A.T. : Reading)--University of the Philippines, Diliman.
Keywords: Reading (Elementary) -- Philippines; Study skills -- Study and teaching (Elementary) -- Philippines